Rhabdomyolysis with acute renal injury in a patient with Covid 19. Case report - Sante Farfán, Giancarlo (2021)
SARS-CoV-2 is an RNA virus that can manifest clinically with pneumonia, neurologic, myocardial and renal involvement as well as with hematologic and multiple organ failure and death. We report the case of a male patient admitted to the ICU severe acute respiratory distress associated to SARS-CoV-2 infection who required mechanical ventilation with pronation and vasopressors. He developed acute kidney injury with reddish urine and serum levels of CK in 17,179 UI/ml consistent with SARS-CoV-2 associated rhabdomyolysis. The patient underwent hemodialysis with complete recovery and subsequent discharge from the ICU.